Total and Cancer Mortality After Supplementation With Vitamins and Minerals: Follow-up of the Linxian General Population Nutrition Intervention Trial - Qiao, You-Lin; Dawsey, Sanford M.; Kamangar, Farin; Fan, Jin-Hu; Abnet, Christian C.; Sun, Xiu-Di; Johnson, Laura Lee; Gail, Mitchell H.; Dong, Zhi-Wei; Yu, Binbing; Mark, Steven D.; Taylor, Philip R. (JNCI : Journal of the National Cancer Institute, 2009)
Background The General Population Nutrition Intervention Trial was a randomized primary esophageal and gastric cancer prevention trial conducted from 1985 to 1991, in which 29 584 adult participants in Linxian, China, were given daily vitamin and mineral supplements. Treatment with “factor D,” a combination of 50 μg selenium, 30 mg vitamin E, and 15 mg beta-carotene, led to decreased mortality from all causes, cancer overall, and gastric cancer. Here, we present 10-year follow-up after the end of active intervention. Methods Participants were assessed by periodic data collection, monthly visits by village health workers, and quarterly review of the Linxian Cancer Registry. Hazard ratios (HRs) and 95% confidence intervals (CIs) for the cumulative effects of four vitamin and mineral supplementation regimens were calculated using adjusted proportional hazards models. Results Through May 31, 2001, 276 participants were lost to follow-up; 9727 died, including 3242 from cancer (1515 from esophageal cancer and 1199 from gastric cancer). Participants who received factor D had lower overall mortality (HR = 0.95, 95% CI = 0.91 to 0.99; P = .009; reduction in cumulative mortality from 33.62% to 32.19%) and gastric cancer mortality (HR = 0.89, 95% CI = 0.79 to 1.00; P = .043; reduction in cumulative gastric cancer mortality from 4.28% to 3.84%) than subjects who did not receive factor D. Reductions were mostly attributable to benefits to subjects younger than 55 years. Esophageal cancer deaths between those who did and did not receive factor D were not different overall; however, decreased 17% among participants younger than 55 (HR = 0.83, 95% CI = 0.71 to 0.98; P = .025) but increased 14% among those aged 55 years or older (HR = 1.14, 95% CI = 1.00 to 1.30; P = .47). Vitamin A and zinc supplementation was associated with increased total and stroke mortality; vitamin C and molybdenum supplementation, with decreased stroke mortality. Conclusion The beneficial effects of selenium, vitamin E, and beta-carotene on mortality were still evident up to 10 years after the cessation of supplementation and were consistently greater in younger participants. Late effects of other supplementation regimens were also observed.